A Reinterpretation of Islamic Law within the Discourse of Muslim Feminism - Reza Fauzi Nazar; Zara Sofia; Amina Sharipova; Herman Herman (Insani: Jurnal Pranata Sosial Hukum Islam, 2026)
The discourse on Muslim feminism has developed as a critical response to the dominance of patriarchal interpretations that have long influenced the construction of Islamic law, particularly in the field of family law. This study aims to analyse the process of reinterpreting Islamic law from a Muslim feminist perspective by developing a methodological framework that integrates uṣūl al-fiqh, contextual hermeneutics, maqāṣid al-sharī‘ah, and an intersectional perspective. This study employs a qualitative approach with a normative-empirical design through literature review and an examination of the dynamics of Islamic legal practice within a contemporary social context. The findings indicate that gender inequality in family law is more a product of historical interpretative constructions than an inherent consequence of normative Islamic texts. Consequently, reinterpretation based on an integrative approach can produce a framework of ijtihād that is more inclusive, contextual and oriented towards substantive justice. The novelty of this study lies in the development of a methodological model that operationally bridges the epistemology of classical Islamic law with the perspective of contemporary Muslim feminism to support family law reform, protect women’s rights, and strengthen the role of religious courts. These findings make a theoretical contribution to the development of multidisciplinary Islamic legal studies, as well as offering practical implications for the formulation of legal policies that are more responsive to gender justice. However, the validity of the developed model still requires empirical testing across various social contexts and legal systems in Muslim countries.